New aspects in the implementation of the quasi-static method for the solution of neutron diffusion problems in the framework of a nodal method. (January 2016) - Caron, D.; Dulla, S.; Ravetto, P.
Highlights: The implementation of the quasi-static method in 3D nodal diffusion theory model in hexagonal- z geometry is described. Different formulations of the quasi-static technique are discussed. The results presented illustrate the features of the various formulations, highlighting advantages and drawbacks. A novel adaptive procedure for the selection of the time interval between shape recalculations is presented. Abstract: The ability to accurately model the dynamic behaviour of the neutron distribution in a nuclear system is a fundamental aspect of reactor design and safety assessment. Due to the heavy computational burden associated to the direct time inversion of the full model, the quasi-static method has become a standard approach to the numerical solution of the nuclear reactor dynamic equations on the full phase space. The present paper is opened by an introductory critical review of the basics of the quasi-static scheme for the general neutron kinetic problem. Afterwards, the implementation of the quasi-static method in the context of a three-dimensional nodal diffusion theory model in hexagonal- z geometry is described, including some peculiar aspects of the adjoint nodal equations and the explicit formulation of the quasi-static nodal equations. The presentation includes the discussion of different formulations of the quasi-static technique. The results presented illustrate the features of the various formulations, highlighting the corresponding advantages and drawbacks. An adaptive procedure for the selection of the time interval between shape recalculations is also presented, showing its usefulness in practical applications.